Impact of financial development on macroeconomic volatility: Does human capital matter? - Mansoor Mushtaq; Gulnaz Hameed; Muhammad Hanif (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
This study adds to the body of literature by investigating the moderating effect of human capital in the association of financial development with macroeconomic volatility in a sample of Asian countries. From 1993 until 2021, annual panel data was collected. For empirical analysis, generalized least squares (GLS) and generalized method of moments (GMM) approaches have been estimated using STATA software. The results of the static and dynamic study demonstrate the detrimental direct as well as indirect effect of financial sector development on macroeconomic volatility via the human capital channel. Macroeconomic volatility is increased by trade openness and inflation, but remittances have a mixed effect. In order to benefit from financial development in terms of reducing macroeconomic instability, human capital is important. In the context of financial development, this study supports the literature's suggestions for fostering the development of human capital to promote sustainable economic growth.
Keywords: 330; Asia; financial development; human capital; inflation; macroeconomic volatility; remittances; trade openness